2016
DOI: 10.1016/j.ssmph.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among white, black, and Hispanic male and female state prisoners, 2001–2009

Abstract: Although much research considers the relationship between imprisonment and mortality, little existing research has tested whether the short-term mortality advantage enjoyed by prisoners extends to Hispanics. We compared the mortality rates of non-Hispanic white, non-Hispanic black, and Hispanic male and female state prisoners to mortality rates in the general population using data from the Deaths in Custody Reporting Program, the National Prisoner Statistics, the National Corrections Reporting Program, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Incarcerated men experienced heightened risk of all-cause mortality across all facility types and nearly all age groups, driven by elevated rates of death from violence, suicide, and communicable diseases. While these findings were consistent with some studies from high-income countries that reported increased risk of homicide [8,38], suicide [39][40][41], and infectious disease deaths [6,10] during incarceration, they contrast with other studies that reported reduced all-cause mortality and homicide during incarceration [5], particularly among subgroups with higher baseline mortality [9,10,42,43]. The root causes of these differences are undoubtedly complex and were not addressed by the present study but may include varying prison conditions, management, and culture.…”
Section: Mortality During Incarcerationsupporting
confidence: 87%
“…Incarcerated men experienced heightened risk of all-cause mortality across all facility types and nearly all age groups, driven by elevated rates of death from violence, suicide, and communicable diseases. While these findings were consistent with some studies from high-income countries that reported increased risk of homicide [8,38], suicide [39][40][41], and infectious disease deaths [6,10] during incarceration, they contrast with other studies that reported reduced all-cause mortality and homicide during incarceration [5], particularly among subgroups with higher baseline mortality [9,10,42,43]. The root causes of these differences are undoubtedly complex and were not addressed by the present study but may include varying prison conditions, management, and culture.…”
Section: Mortality During Incarcerationsupporting
confidence: 87%